2015
DOI: 10.1053/j.gastro.2015.05.039
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Nonalcoholic Fatty Liver Disease in Adolescents Undergoing Bariatric Surgery

Abstract: Background & Aims Little is known about the prevalence of nonalcoholic fatty liver disease (NAFLD) among severely obese adolescents or factors that determine its development. We investigated the prevalence of NAFLD in a multicenter cohort of adolescents undergoing bariatric surgery and factors associated with it. Methods We enrolled 242 adolescents undergoing bariatric surgery between March 2007 and February 2012 at 5 tertiary care centers into a multicenter, prospective observational cohort study. Intra-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 40 publications
1
110
0
Order By: Relevance
“…Beyond these changes in circulating biomarkers, tissuespecific inflammation in obese children parallels what is seen in obese adults. NAFLD is present in 59% of adolescents referred for bariatric surgery, with 10% of these showing evidence of nonalcoholic steatohepatitis (NASH) (89). Severity of NAFLD in this cohort correlated with wbc count, and liver samples from adolescents with NASH had increased expression of genes involved in macrophage chemotaxis.…”
Section: When Does Metainflammation Begin?mentioning
confidence: 79%
“…Beyond these changes in circulating biomarkers, tissuespecific inflammation in obese children parallels what is seen in obese adults. NAFLD is present in 59% of adolescents referred for bariatric surgery, with 10% of these showing evidence of nonalcoholic steatohepatitis (NASH) (89). Severity of NAFLD in this cohort correlated with wbc count, and liver samples from adolescents with NASH had increased expression of genes involved in macrophage chemotaxis.…”
Section: When Does Metainflammation Begin?mentioning
confidence: 79%
“…Adolescents selected for extreme obesity may be biologically different that children with NAFLD who are seen in gastroenterology clinics. In the multi-center Teen LABS Study of adolescents undergoing bariatric surgery, 148 had intraoperative liver biopsies and the prevalence of NAFLD in this cohort was 59%, with only 10% of those with NAFLD having definite NASH and 0.7% having advanced fibrosis [22]. …”
Section: Introductionmentioning
confidence: 99%
“…10 However, Results from different studies show that the prevalence of NAFLD varies between 16.7% and 96% in morbidly obese patients subjected to bariatric surgery. [10][11][12][13][14][15][16][17][18][19][20][21][22] The wide range of NAFLD prevalence depends on the biochemical criteria and the method sensitivity used to detect NAFLD. 8,23 Furthermore, NASH, as a progressive manifestation of NAFLD, occurs in 7.3% to 98% of such patients.…”
Section: Prevalence Of Nafld and Nash In Bariatric Candidatesmentioning
confidence: 99%
“…8,23 Furthermore, NASH, as a progressive manifestation of NAFLD, occurs in 7.3% to 98% of such patients. 10,12,13,17,18,[20][21][22][24][25][26][27][28][29][30] The study which reported NASH in 98% of their patients, indicated that the mean super obese state (Mean BMI 52.8 kg ⁄m 2 ) in their population is the reason of high NASH prevalence. 30 Another study concluded that the differences in NASH prevalence can be explained by the histological criteria used to diagnose NASH.…”
Section: Prevalence Of Nafld and Nash In Bariatric Candidatesmentioning
confidence: 99%